Multiparametric real‐time sensing of cytosolic physiology links hypoxia responses to mitochondrial electron transport. Issue 4 (18th September 2019) - Wagner, Stephan; Steinbeck, Janina; Fuchs, Philippe; Lichtenauer, Sophie; Elsässer, Marlene; Schippers, Jos H. M.; Nietzel, Thomas; Ruberti, Cristina; Van Aken, Olivier; Meyer, Andreas J.; Van Dongen, Joost T.; Schmidt, Romy R.; et al.
Summary: Hypoxia regularly occurs during plant development and can be induced by the environment through, for example, flooding. To understand how plant tissue physiology responds to progressing oxygen restriction, we aimed to monitor subcellular physiology in real time and in vivo . We establish a fluorescent protein sensor‐based system for multiparametric monitoring of dynamic changes in subcellular physiology of living Arabidopsis thaliana leaves and exemplify its applicability for hypoxia stress. By monitoring cytosolic dynamics of magnesium adenosine 5'‐triphosphate, free calcium ion concentration, pH, NAD redox status, and glutathione redox status in parallel, linked to transcriptional and metabolic responses, we generate an integrated picture of the physiological response to progressing hypoxia. We show that the physiological changes are surprisingly robust, even when plant carbon status is modified, as achieved by sucrose feeding or extended night. Inhibition of the mitochondrial respiratory chain causes dynamics of cytosolic physiology that are remarkably similar to those under oxygen depletion, highlighting mitochondrial electron transport as a key determinant of the cellular consequences of hypoxia beyond the organelle. A broadly applicable system for parallel in vivo sensing of plant stress physiology is established to map out the physiological context under which both mitochondrial retrograde signalling and low oxygen signalling occur, indicating shared upstream stimuli.